Una aproximación al régimen de los funcionarios - Sarmiento Larrauri, José Ignacio (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
A brief history of our Civil Servant System is outlined here. It begins with the approval of the Spanish Constitutional Law and considers the different attempts of reformation, including those merely analysed in Cabinets and those published in the Bulletin of Parliament. And far beyond that, it briefly analyses the present situation and the uncertain future of our Civil Servant Model, because of the invasion of Labour Laws in the civil servant area.